Kant's Concept of Law. (27th December 2018) - Capps, Patrick; Rivers, Julian
Abstract: Kant's Doctrine of Right is often understood to explain the authority of law by reference to the way law secures important general interests such as security and welfare. In this article we show that rooting legal obligation in the instrumental benefits conferred by law is a misreading of Kant's argument. Instead, we suggest that at the center of Kant's sophisticated and multifaceted legal philosophy is a moral concept of law, or Right, which has interpretative priority. Kant's argument for Right demonstrates that the establishment of an omnilateral will is the only way for persons' wills to be aligned consistently with the categorical moral duties they owe to each other. Right can never be secured unilaterally, but only given effect by a constitution which secures various democratic and substantive (innate) rights. This explains Kant's opposition to despotism, colonialism and revolution. We distinguish this moral concept of law from related juridical (i.e., positive) and ethical concepts, and we trace some of the complex relationships which exist between juridical law and the moral concept which, in Kant's words, gives law its brain.